Health Facilities Safety Assurance Improvement through the Establishment of a Testing and Calibration Institution in Riau Province - Rino Ferdian Surakusumah; Nur Hadziqoh; Yeni Pertiwi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
One of the important parameters of providing health services to the community is the availability of adequate medical devices. To ensure safety and accuracy, medical devices must be tested and calibrated periodically by the Health Facility Testing Institution (IPFK) which has obtained permission from the Ministry of Health. The island of Sumatra, which is one of the large islands in Indonesia which has many health facilities, currently only consists of one Health Facility Security Center (BPFK). Therefore, to improve safety assurance in health facilities in the Sumatra region, it is necessary to establish new IPFKs that can provide testing and calibration services for medical devices. The purpose of this activity is to establish IPFK in Pekanbaru, Riau to improve the safety of patients and users' assurance of medical devices in health facilities. This activity refers to the procedures established by the Ministry of Health. Some of the activities carried out were developing company deeds, business plans, organizational structure, human resource (HR) needs and infrastructure, recruiting HR, conducting HR training, developing quality assurance documents, developing operational authorization application documents, and applying for operational authorization to the Ministry of Health. The activity was carried out for approximately one year and succeeded in establishing an IPFK that had adequate human resources, infrastructure, and quality documents and obtained an operational permit from the Ministry of Health.